The Evolving Role of Primary Care Practitioners in Dermatology: Current Status and Emerging Educational Resources. Issue 6 (November 2015) - Beroukhim, Kourosh; Nguyen, Catherine; Danesh, Melissa J.; Wu, Jashin J.; Koo, John
Abstract : ABSTRACT: Skin disorders account for a significant portion of cases managed by primary care practitioners (PCPs). However, previous studies show that PCPs are inadequately trained for this role and are significantly less effective than board-certified dermatologists with respect to the diagnosis and treatment of cutaneous disorders. This is most concerning in regard to life-threatening skin diseases such as malignant melanomas, which must be correctly diagnosed and treated in a timely manner. Increasing the coverage of cutaneous disorders during medical school and residency would likely improve the proficiency of future PCPs with respect to dermatological disorders. Similarly, practicing PCPs face a shortage of dermatology educational resources that are compatible with their busy schedules. To address this need, novel resources such as Internet-based continuing medical education courses, point-of-care decision support software, and teledermatology are being further developed to promote the delivery of precise and cost-effective healthcare in the primary care setting. In addition, the greater need for dermatology PCPs has been met with a rise in the role of dermatology nurse practitioners.